Rotor position synchronization control methods in central-converter multi-machine architectures with application to aerospace electrification - Lima, Cláudio de Andrade, author; Cale, James, advisor; Chong, Edwin, committee member; Herber, Daniel, committee member; Kirby, Michael, committee member (Colorado State University. Libraries, 2024)
With the continuous advancement of the aerospace industry, there has been a significant shift towards More Electric Aircraft (MEA). Some of the advantages of the electrification of some actuation systems in an aircraft include lower weight --- hence, lower fuel consumption, --- robustness, flexibility, ease of integration, and higher availability of sensors to achieve better diagnostics of the system. One cannot ignore the challenges of the electrification process, which encompasses finding appropriate hardware architectures, and control schemes, and obtaining at least the same reliability as traditional drives. The thrust reverser actuation system (TRAS), which acts during landing to reduce the necessary runway for the aircraft to fully decelerate, has a big potential to be replaced by an electromechanical version, the so-called EM-TRAS. Among the different hardware architectures, the central-converter multi-machine (CCMM) stands out for employing a single power converter that drives multiple machines in parallel, saving weight and room usage inside the aircraft. This solution comes with its challenges related to the requirement of ensuring position synchronization among all the machines, even under potentially unbalanced mechanical loads. Since there is only one central converter, all the machines are subject to its common output, limiting the control independence of each machine. Moreover, the lack of position synchronization among the machines can cause harmful stresses to the mechanical structure of the EM-TRAS. This work proposes a solution for position synchronization under CCMM architectures, for aerospace applications. The proposed method utilizes three-phase external and variable resistors connected in series with each of the machines, which increases the degrees of freedom (DOF) to control independently each machine under different demands. Mathematical modeling for the different components of the system is presented, from which the proposed solution is derived. Numerical simulations are used to show the working capabilities of the external resistor method. The performance of the position synchronization is enhanced via H-infinity control design methods. Hardware experiments are also presented, obtained from an experimental testbed that was partially designed and constructed during this work. Both numerical and experimental results are in agreement. Initial findings show that the method is promising and works well under some operating conditions. However, some limitations of the method are presented, such as the unstable operation under negative loads. An alternative position synchronization method for CCMM systems is proposed at the end of this work. The method is based on independently controlled induced voltages on each machine's power cables through low-power auxiliary converters and three-phase compact transformers, resulting in independent terminal voltages applied to each machine. This work describes the method and validates it through numerical simulations. Initial findings show that the method overcomes some of the limitations of the external resistors method, while keeping -- and, in some cases, improving -- the overall performance in terms of convergence time and peak position error.
Keywords: aircraft electrification; optimal control; aerospace testbed; rotor position synchronization; induction machines